TIME MANAGEMENT AND LEARNING DISCIPLINE AS DETERMINANTS OF ACADEMIC SUCCESS AMONG STUDENT ACTIVISTS - Sari, Diah Kumala; Kartikowati, Rr Sri; Maulida, Ervina (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
This study aims to determine the effect of time management and learning discipline on academic achievement. This study uses a quantitative approach with a questionnaire data collection technique in a Google form with a Likert scale of 1-5. The population in this study were 743 student activists at the Faculty of Economics and Business, Universitas Negeri Jakarta, using the Taro Yamane formula with a 5% error tolerance level, resulting in a sample of 260 respondents. Data processing was carried out using the statistical application Statistical Product and Service Solutions (SPSS) version 27. The results of the study indicate that time management and learning discipline influence academic achievement partially and simultaneously. The results of this study indicate that the coefficient of determination of the influence of time management and learning discipline contributes 73% to academic achievement, while the other 27% is influenced by other factors that have not been studied.